“Ritornare” nella post-migrazione: narrazioni sull’abitare translocale a Serino (AV) - Post-Migration “Return”: Translocal Living Narratives from Serino (AV), Italy - Daria De Grazia (EtnoAntropologia)
This article presents preliminary findings from ethnographic research in Serino (Southern Italy), examining post-migration returns as multidirectional, translocal processes. Rather than definitive endpoints, return mobilities emerge as intergenerational practices of reterritorialization. Through life histories, the study explores how identities, belonging, and place are negotiated across temporal and spatial scales, reshaping localities through memory, affect, and transnational entanglements.